2009
DOI: 10.1051/kmae/2010003
|View full text |Cite
|
Sign up to set email alerts
|

The impact of signal crayfish (Pacifastacus leniusculus) on the recruitment of salmonid fish in a headwater stream in Yorkshire, England

Abstract: Key-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 26 publications
0
55
0
1
Order By: Relevance
“…Further longer-term studies of the population level consequences of crayfish invasion are required. Several studies have found lower populations in the presence of signal crayfish (Guan and Wiles 1997;Peay et al 2009), whereas others have not (Stenroth and Nyström 2003;Degerman et al 2007); comprehensive studies of fish populations pre-to post-invasion and assessed relative to the 'natural state' (i.e. with the presence of native crayfish) are required to address this question.…”
Section: Discussionmentioning
confidence: 99%
“…Further longer-term studies of the population level consequences of crayfish invasion are required. Several studies have found lower populations in the presence of signal crayfish (Guan and Wiles 1997;Peay et al 2009), whereas others have not (Stenroth and Nyström 2003;Degerman et al 2007); comprehensive studies of fish populations pre-to post-invasion and assessed relative to the 'natural state' (i.e. with the presence of native crayfish) are required to address this question.…”
Section: Discussionmentioning
confidence: 99%
“…Field surveys in rivers revealed negative relationships between the abundance of crayfish and the abundance of benthic fishes (Guan and Wiles 1997;Bubb et al 2009;Peay et al 2009). From a long term survey, Wilson et al (2004) found that the invasion of rusty crayfish (Orconectes rusticus Girard) also decreased the density of non-predatory fish in a northern lake.…”
Section: Introductionmentioning
confidence: 99%
“…White-clawed crayfish have been known to alter the Irish lake habitat by macrophyte reduction (Matthews and Reynolds, 1992;Matthews et al, 1993) and to modify the macroinvertebrate food web (Matthews et al, 1993). There is some reciprocal predation on juvenile stages; trout eat small crayfish, while white-clawed crayfish may eat salmonid eggs and alevins (Peay et al, 2009) and other small fish, including adult stickleback (Reynolds and O'Keeffe, 2005).…”
Section: Interactions Between Indigenous Crayfish Species (Ics) and Fishmentioning
confidence: 99%
“…The range of environmental impacts of signal crayfish has been reviewed by Everard et al (2009). While impacts on fish have not been seen in Sweden (Söderbäck, 1994), signals have been shown to be deleterious to salmonids in UK (Peay et al, 2009). In Britain, since their introduction in the late 1970s, signal crayfish have become increasingly widespread in rivers, causing negative impacts on communities of aquatic plants, invertebrates and benthic fish.…”
Section: > Signal Crayfish Pacifastacus Leniusculusmentioning
confidence: 99%
See 1 more Smart Citation